2010
DOI: 10.2341/09-244-l
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Contamination on Microtensile Bond Strength to Dentin of Three Self-etch Adhesives

Abstract: This study evaluated the effects of blood contamination and decontamination methods during different steps of bonding procedures on the microtensile bond strength of two-step self-etch adhesives to dentin. Sixty extracted human molars were ground flat to expose occlusal dentin. The 60 molars were randomly assigned to three groups, each treated with a different two-step self-etch adhesive: Clearfil SE Bond, AdheSE and Tyrian SPE. In turn, these groups were subdivided into five subgroups (n = 20), each treated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 20 publications
3
32
0
3
Order By: Relevance
“…Bond strength of bonding systems to dentin is negatively influenced by blood contamination 10,29,30) . The manufacturer produced many haemostatic agents to stop the bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Bond strength of bonding systems to dentin is negatively influenced by blood contamination 10,29,30) . The manufacturer produced many haemostatic agents to stop the bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[1–3] Any contamination of the prepared surface by saliva, blood or gingival crevicular fluid should be avoided in order to achieve a successful and durable bond between the resin composite and the tooth. [45] Achieving good moisture control is a common problem encountered in restorative dentistry, especially when rubber dam isolation is not feasible. [26] Many carious lesions are found in areas where it is difficult to obtain appropriate isolation for the use of dentin bonding agents, especially when the site is near or at the gingival margin.…”
Section: Introductionmentioning
confidence: 99%
“…[47] Several recent studies suggested that self-etch adhesives may be more resistant to salivary contamination because hydrophilic adhesive solutions, specifically products with acetone or ethanol based, may displace or diffuse through the salivary film to reach the underlying hydroxyapatite or collagen. [248] However, the effect of blood contamination on the adhesive properties of 1-step self-etching adhesives has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, como já mencionado, restaurar essas lesões com resina composta apresenta uma série de dificuldades técnicas que podem afetar os resultados clínicos. Dificuldades no isolamento, na adesão com a margem da dentina e o estresse de contração de polimerização levam a que realizar esses trabalhos seja considerado um procedimento extremamente sensível [26][27] . O cimento de ionômero de vidro tem sido bem usado devido à sua adesão química com a estrutura dentária e liberação de flúor [28][29] , além de ser uma técnica relativamente simples comparada à da resina.…”
Section: Tabela 1 -Avaliação Clínica Das Restaurações Classe V (N = 4unclassified